A PHOTOMETER - Pereversentsev, A. F.; Komarov, N. S.; Arkhipov, M. G.; Depenchuk, E. A.; Ivanov, V. N.; Ryabov, A. V. (Одеські астрономічні публікації, 2017)
One-channel photometer is presented on the basis of a personal-professional computer designed for receiving information in 6 filters. It has control of a photoelectron tract by means of a radio luminescence source. Information is brought out to the display and a file. The photoreceiver is cooled and thermostated. The maximum cooling amounts to 230K with ±0.5-precision of maintenance. The time of information accumulation ranges from 10 ms to 10 s with the discreteness of 10 ms.